2014
DOI: 10.1111/ijlh.12268
|View full text |Cite
|
Sign up to set email alerts
|

Basic evaluation of Pentra MS CRP, a new automated hematology analyzer for rapid 5‐part WBC differential and CRP using a small volume of whole blood

Abstract: Pentra MS CRP is a convenient and reliable analyzer especially in the emergency unit of hospitals in which the prompt and simultaneous measurement of CBC including 5-Diff and CRP is often necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 14 publications
(20 reference statements)
2
14
1
Order By: Relevance
“…Indeed, all of the peripheral blood smears prepared from the 5 MDS patients with decreased mean light absorbance (MLA) in neutrophils showed a reduced SBB score in this study. On the other hand, there was definite selection bias in the present study, namely these five patients showed a discrepancy in MON (%) between Pentra MS CRP and the manual microscopic differential in our previous study . Therefore, they were enrolled in the present study to clarify the reason for this discrepancy, and the down‐deviation of neutrophil scattergrams due to decreased light absorbance seemed to be one of the major reasons for such a discrepancy between Pentra MS CRP and the manual microscopic method.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Indeed, all of the peripheral blood smears prepared from the 5 MDS patients with decreased mean light absorbance (MLA) in neutrophils showed a reduced SBB score in this study. On the other hand, there was definite selection bias in the present study, namely these five patients showed a discrepancy in MON (%) between Pentra MS CRP and the manual microscopic differential in our previous study . Therefore, they were enrolled in the present study to clarify the reason for this discrepancy, and the down‐deviation of neutrophil scattergrams due to decreased light absorbance seemed to be one of the major reasons for such a discrepancy between Pentra MS CRP and the manual microscopic method.…”
Section: Discussioncontrasting
confidence: 58%
“…Therefore, Pentra MS CRP seemed less sensitive to dysplastic erythrocytes compared with ADVIA 2120, and we might miss some patients with refractory anemia in the previous study. As another problem, Pentra MS CRP might present the false positivity when the absolute number of neutrophils in the sample was extremely low to produce the appropriate neutrophil scattergrams for this analysis . Moreover, MLA might be decreased in certain diseases other than MDS, although we have not detected such patients so far.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, we included a step to judge the need to merge close-by clusters. 2 closely associated clusters are merged when the data size of 1 cluster is less than a critical size (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) or when the distance between the 2 cluster centers is below a critical limit (i.e., the lower 1 percentile of all Euclidean distances between k cluster centers and N data points: k × N distances).…”
Section: Optional Operation For Merging Clustersmentioning
confidence: 99%
“…We had an opportunity to develop a new clustering algorithm to the feasibility of upgrading the software currently in use in a hematology analyzer, the Horiba Pentra MS CRP [7], so that it can cope with the above situations, which are often processed as difficult cases with a warning from the analyzer requesting the special attention of a hematologist. This new clustering method consists of a series of algorithms to handle various situations.…”
Section: Introductionmentioning
confidence: 99%